2017
DOI: 10.20937/rica.2017.33.esp01.13
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND SCREENING OF BACTERIA FROM Zea mays PLANT GROWTH PROMOTERS

Abstract: Plant growth promoting rhizobacteria is a beneficial microbe colonizing plant roots, which enhances crop productivity and offers an attractive way to replace chemical fertilizers, pesticides, and supplements. In Mexico, the corn (Zea mays L.) is an important annual gramineae crop with a high volume of global production because of the favorable environmental and socioeconomic situation. In this study the isolation of new strains of bacteria under different environmental conditions will enable further research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
(32 reference statements)
1
5
0
1
Order By: Relevance
“…Regard the in vitro plant growth promoter potential of the isolated strains, a nitrogen-fixing bacteria predominance (81%) was observed (Table 1). These results concur with reports of rhizospheric soils from corn (Toribio-Jiménez et al, 2017;Karnwal, 2017, Richard et al, 2018. In the production of indoloacteic acid (IAA), only 25% of the strains had this activity, the statistical analysis determined significant differences between them.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Regard the in vitro plant growth promoter potential of the isolated strains, a nitrogen-fixing bacteria predominance (81%) was observed (Table 1). These results concur with reports of rhizospheric soils from corn (Toribio-Jiménez et al, 2017;Karnwal, 2017, Richard et al, 2018. In the production of indoloacteic acid (IAA), only 25% of the strains had this activity, the statistical analysis determined significant differences between them.…”
Section: Resultssupporting
confidence: 90%
“…From the total isolates, 62.5% (10 strains) were Grampositive, the remaining Gram-negative (Table 1). Similarly, Toribio-Jiménez et al (2017) and Abedinzadeh et al (2019) reported a higher number of Gram-positive in corn. The 56% of the isolated strains were aerobic or catalase-positive, similar to those reported by Karnwal (2017).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This could be due to these bacteria could produce organic acids such as gluconic acid, lactic acid, succinic acid, formic acid, malic acid, citric acid, oxalic acid, acetic acid or tartaric acid. These organic acids could help to dissolve efficiently not only the insoluble silicate minerals but also insoluble phosphate minerals and become the soluble one for bacteria and plant to absorb for their growth (Khan et al, 2014) and the outcome of the previous studies showed that Citrobacter freundii had another function in phosphate solubilization in liquid medium containing Ca 3 (PO 4 ) 2 as phosphorus source and Klebsiella aerogenes as well in phosphate solubilization (Toribio-Jiménez et al, 2017;Samina et al, 2010). However, these bacteria's function in phosphate solubilization for AlPO 4 and FePO 4 as phosphorous sources for bacteria has still not published yet.…”
Section: Discussionmentioning
confidence: 99%
“…B. licheniformis is recognized by multiple biotechnological applications such as: 1) bioremediation of sites contaminated by pesticides, fertilizers, hydrocarbons and heavy metals, 2) biological control in the development of biofungicides due to antifungal activity, 3) concrete production for its ability to precipitate calcium carbonate, and 4) biofertilizers for the characteristics of plant growth promotion [14]. B. licheniformis M2-7, is a mobile, facultative anaerobic, and thermoresistant bacterium isolated from hot springs [15].…”
Section: Introductionmentioning
confidence: 99%